A New Antiviral Flavone Glycoside from Vernonia cinerea Less. - Yadava, R.N.; Raj, Mamta (Asian Journal of Chemistry, 2013)
A new flavone glycoside (A) m.p. 258-260 ºC, m.f. C33H40O19, [M]+ 740 (FABMS), has been isolated from roots of Vernonia cinerea Less. It was characterized as 5,7,4'-trihydroxy 3'-methoxy flavone-4'-O-a-L-rhamnopyranosyl-(1®4)-O-a-L-arabino-pyranosyl-(1®3)-O-b-D-galactopyranoside by various chemical degradations and spectral analysis which showed antiviral activity alongwith two known compounds luteolin (B) and taxifolin (C).